Correlation of IL-10 Levels with the Bacterial Index in Multibacillary Leprosy - Fitriyanti, Fitriyanti; Lipinwati, Lipinwati; Istarini, Attiya; Ekaputri, Tia Wida; Nastiti, Niken Irfa; Adnyana, I Made Dwi Mertha (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: Multibacillary (MB) leprosy is characterised by a high bacillary burden and a tolerogenic immune profile. Interleukin-10 (IL-10) is a key immunoregulatory cytokine that may reflect bacillary load. Objective: To compare bacillary burden and IL-10 between MB patients and controls and to examine the correlation between the Bacterial Index (BI) and IL-10 among MB patients. Methods: A comparative cross-sectional study included 68 participants (MB n=34; controls n=34). Categorical variables were analysed using Chi-square tests, and medians were used with Mann–Whitney U tests. Spearman’s rank correlation was used to assess the BI–IL-10 relationship in MB. Results: Age distribution was similar between groups (p=0.451), whereas occupation (p=0.040) and education (p=0.027) differed. BI was markedly higher in MB than in controls (median 2.5 [IQR 4] vs 0 [0]; p<0.001). IL-10 concentrations were also higher in MB (1.96 [4.03] pg/mL) than in controls (1.12 [1.94] pg/mL; p=0.029). Among MB patients, BI correlated positively with IL-10 (ρ = 0.358; p = 0.038). Conclusion: MB leprosy shows substantially greater bacillary burden and elevated IL-10 relative to controls. The positive association between BI and IL-10 supports the role of an immunoregulatory milieu linked to bacillary load. These findings highlight IL-10 as a potential biomarker for disease burden in MB leprosy and warrant validation in larger, adjusted cohorts.